We are asked to solve:
I know this is simple, but im reallly rusty. So what I tried to do is get rid of the x-3 by multiply both sides by it
=
Then I moved the variables to one side and the integers to another:
Then I divided both sides by -3
Was this the correct method of solving these?
Just to add - what you solved for was f(x)=1, not f(x) =0. Some advice: always double-check your work, in this case by substituting x=-11/3 back into the original equation to see if it works out. If you put x=-11/3 into the equation you get:
From this you can see that your answer i incorrect.